Crop Choice, Drought and Gender: New Insights from Smallholders' Response to Weather Shocks in Rural Uganda. (10th February 2021) - Agamile, Peter; Dimova, Ralitza; Golan, Jennifer
Abstract: We analyse gender differences in the response of smallholder farmers to droughts, taking the duration and severity of the event into account. Using a novel weather shock measure that combines spatial rainfall data with detailed cropping calendars, survey data from Uganda and standard econometric techniques, we find that adverse weather events provide an opportunity for women to enter the commercial crop market by allocating land from subsistence to income generating crops. This counterintuitive pattern is, in part, explained by the greater propensity of men to allocate time to non‐agricultural activities in the event of weather shocks.